Scapular dyskinesia and its influence on painful shoulder syndromes: a narrative review (Research, Society and Development, 2025)
This study aims to investigate whether this condition can be considered a predictive factor for the development of such syndromes, contributing to more effective prevention and rehabilitation strategies. This research analyzed the relationship between scapular dyskinesis and painful shoulder conditions, such as impingement syndrome. Dyskinesis, characterized by the irregular displacement of the scapula during humeral movement, may contribute to biomechanical alterations and potential structural damage. Its clinical evaluation includes static and dynamic inspection, allowing for the identification of dysfunctional patterns that guide rehabilitation strategies, such as muscle strengthening and stretching. A review of studies published between 1990 and 2024 indicated that, although dyskinesis may represent a risk factor for impingement syndrome, its presence is not definitive, as it may also result from mechanical adaptations to preexisting pain. Therefore, the clinical approach should consider both its influence on dysfunction development and its role as an adaptive response. This research theoretically contributes to a broader understanding of scapular dyskinesis and, in practice, provides insights to enhance professional assessment and intervention. It is concluded that early identification and appropriate rehabilitation are essential to minimize the impacts of dyskinesis and optimize shoulder functionality.